2016
DOI: 10.1080/15476286.2016.1245268
|View full text |Cite
|
Sign up to set email alerts
|

Full-length sequence assembly reveals circular RNAs with diverse non-GT/AG splicing signals in rice

Abstract: Circular RNAs (circRNAs) have been identified in diverse eukaryotic species and are characterized by RNA backsplicing events. Current available methods for circRNA identification are able to determine the start and end locations of circRNAs in the genome but not their full-length sequences. In this study, we developed a method to assemble the full-length sequences of circRNAs using the backsplicing RNA-Seq reads and their corresponding paired-end reads. By applying the method to an rRNA-depleted/RNase R-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 40 publications
2
83
0
Order By: Relevance
“…circRNAs are widespread and diverse in both animals and plants and have potential regulatory functions . In plants, circRNAs are closely associated with development and stress-induced responses Ye et al, 2015Ye et al, , 2017. Here, we demonstrated that circRNAs are involved in the rice-M. oryzae interaction.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…circRNAs are widespread and diverse in both animals and plants and have potential regulatory functions . In plants, circRNAs are closely associated with development and stress-induced responses Ye et al, 2015Ye et al, , 2017. Here, we demonstrated that circRNAs are involved in the rice-M. oryzae interaction.…”
Section: Discussionmentioning
confidence: 76%
“…Since alternative back splicing is required for the biogenesis and diversification of circRNAs in rice Ye et al, 2017), we hypothesized more diverse circRNAs in IR25 may be attributed to more complicated alternative splicing in IR25 than in LTH. Therefore, we annotated the downstream 59 back-splice sites and upstream 39 back-splice sites from all the identified circRNAs.…”
Section: Alternative Splicing Contributes To the Increased Circrna DImentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing data have shown that a variety of organisms could generate circRNAs by back-splicing, including Drosophila [25], rice [26], silkworm [27], zebrafish [28], and humans [29]. In addition to cellular transcripts, viral transcripts were found to form circRNAs in KSHV-infected primary effusion lymphoma cells, EBV-infected cells [20,21] or HPV16 [23].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some methods such as circseq_cup [23] and the oven-fresh CIRC-full method[24] can generate full-length sequence for circRNA however only after the BSJ determination, which the accuracy and integrity of the circRNA sequences are largely not validated yet. Since there is still lack of a benchmark or gold standard to evaluate circRNA detection fairly, only a small portion of circRNAs predicted by the reference-based methods can be experimentally validated [23]. Moreover, accurate detection and quantification of circRNA isoforms for a definite BSJ is far beyond the scope of current methods.…”
Section: Introductionmentioning
confidence: 99%